Comparison of performance-related physical fitness and anaerobic power between Korean wheelchair badminton national and backup players - Kim, J.-T.; Shin, Y.-A.; Lee, K.-H.; Rhyu, H. S. (Journal of Exercise Rehabilitation, 2019)
The purpose of this study was to compare performance-related physical fitness factors and anaerobic power between national and backup players to enhance the performance of wheelchair badminton players and to discover and foster new athletes. This study included 12 wheel-chair badminton players divided into two groups: national players (n=7) and backup players (n=5). Collected data included cardiorespiratory endurance, muscle endurance, muscle strength, power, agility, and anaerobic power. Results indicated that the national players achieved a significantly higher level of muscle endurance, peak power, and mean power than the backup players. Although none of the parameters showed statistically significant differences, the performance levels of the national players were higher than those of the backup players. Because the physical fitness aspects of wheelchair players vary according to their ability and are essential factors, individualized training programs for enhancing performance and preventing injuries among wheelchair badminton players should be developed.